Body composition analysis of athletes from the elite of Brazilian soccer players - José Gerosa-Neto; Fabricio Eduardo Rossi; Camila Buonani da Silva; Eduardo Zapaterra Campos; Rômulo Araujo Fernandes; Ismael Forte Freitas Júnior (Desafio Singular, 2014)
This study analyzed the body composition and bone mineral density of elite Brazilian soccer players and compared its differences according to the player position. Eighty-two soccer players competing at Brazilian first division were split according to their field positions: Goalkeepers (GK, n= 10), Back-fielders (BF, n= 10), Lateral-midﬁelders (LM, n= 15), Central-midﬁelders (CM, n= 25), Forwards (FW, n= 22), and a Control Group (CG, n= 72) of university students. To estimate fat free mass (FFM), fat mass (FM), percentage of body fat (%FM), fat free mass of legs (FFM-Legs) and bone mineral density (BMD), a DEXA was selected. The positions LM (10.5 ± 5.2), CM (9.7 ± 4.0) and FW (9.9 ± 4.4) had lower values of FM and %FM than the GK (17.3 ± 6.0) and the control group (15.0 ± 5.3). Compared to the other positions, FFM was higher in the GK (68.2 ± 10.9) and BF (64.6 ± 6.8) (p< 0.05). All the soccer players were different from the CG (p< 0.05). Soccer players have an FFM, FFM-Legs and BMD significantly higher and FM and %FM lower than the control group.